Program PetroCaribe sebagai Strategi Ekonomi Venezuela Era Presiden Nicolas Maduro - Debby Aurellia; Yasinta D. Febriana; N. Salaeh (Jurnal Hubungan Internasional, 2019)
PetroCaribe is an oil organization initiated by Venezuela for countries inthe Caribbean region as a mean to economic diplomacy and overcomethe oil crisis within the country. Furthermore, PetroCaribe aims to provideoil to countries in the Caribbean at low prices. This study aims tofind out the reasons behind the retention of PetroCaribe as a way to overcomethe economic crisis in Venezuela, and the influence of the existenceof PetroCaribe on countries in the Caribbean region. The approachused in this study is the liberal institutionalist theory, which regardsthe state as a selfish rational actor in operating internationally so thatagreements cannot be enforced hierarchically. Therefore, internationalorganizations can only expect cooperation to occur if the states havethe same interests. This is where PetroCaribe become useful as a formof organization that accommodates the cooperation of the Venezuelanstate as the main actor with Caribbean countries in the economic field. Themethod used in this study is qualitative and descriptive.